A HOLISTIC APPROACH OF RELATIONSHIP MARKETING IN LAUNCHING LUXURY NEW PRODUCTS - Mihoc Florin; Pop Liviu N.; Pop Nicolae Al.; Fotea Ioan S. (Annals of the University of Oradea: Economic Science, 2009)
On the basis of increased complexity of the exchange mechanism, at the beginning of the third millennium the contemporary marketing suffers some physiognomic changes. Holistic orientation of the contemporary marketing is imposed by the new dimensions the